THE EFFECTIVENESS OF THE HEALTHY KITCHEN PROGRAM TO OVERCOME STUNTING IN IMPROVING THE NUTRITIONAL STATUS OF STUNTING TODDLERS - Sridefi, Fadhilla Puja (Majalah Kedokteran Andalas, 2023)
Stunting is a problem of chronic malnutrition which is caused by a lack of nutritional intake for a long time. One of the programs initiated by the BKKBN to reduce stunting rates is the Healthy Kitchen to Overcome Stunting (DASHAT) program. One of the DASHAT programs is providing local supplementary food to stunted toddlers. The aim of this research was to determine the effectiveness of DASHAT on weight gain and nutritional status of stunted toddlers during the program and after 3 months of completion of the program. This research uses a Quasy Experiment approach. The population in this study were all stunted toddlers who received the DASHAT program, while the sample in this study was 34 toddlers taken by random sampling in three areas of the South Padang District Health Center, Padang City. The results of this research show that the DASHAT program is effective in increasing the weight of toddlers with a p-value of 0.000 during the program and 0.048 after the program, but is not effective in changing nutritional status (TB/U) after the DASHAT program ends. Maximum monitoring is needed from various parties regarding stunting toddlers after the DASHAT program is completed.